The Population of Singapore (Third Edition) - Saw, Swee-Hock, 1931-2021 (Book collections on Project MUSE., 2012)
The third edition of this book presents a most comprehensive and up-to-date analysis of population trends and patterns in Singapore since its foundation in 1819 to the present day. Separate chapters are devoted to population growth and distribution, changing population structure, migration, mortality trends and differentials, marriage trends and patterns, divorce trends and patterns, fertility trends and differentials, family planning, abortion and sterilisation, fertility policies and programmes, immigration policies and programmes, labour force and future population trends. The strength of t.